Systems Analysis and Design, 12th Edition - Scott Tilley (Cengage Learning, 2019)
Introduce information systems development with today's latest practical and streamlined approach in Tilley's SYSTEMS ANALYSIS AND DESIGN, 12E and MindTap digital resources. Students learn even more about emerging technologies and methodologies, including agile methods, cloud computing and mobile applications, as this edition provides an easy-to-understand approach to systems analysis and design. Meaningful projects, insightful assignments and end-of-chapter exercises -- within this edition and online -- work together to hone your students' skills. Detailed instructor support focuses on the most important skills and concepts to guide you in helping your students succeed in today's competitive business world.